Paleoenvironmental characteristics and organic matter enrichment mechanisms of the upper Ordovician-lower Silurian organic-rich black shales in the Yangtze foreland basin, South China - Zhao, Liang; Li, Yong; Zou, Chengjie; Zhao, Shaoze; Wu, Chaorong (Frontiers in Earth Science, 2023)
The Wufeng Formation-Longmaxi Formation (O3w-S1l1) black shales within the Yangtze foreland basin (South China) hold significant potential as unconventional oil and gas resources. However, several challenges, including sluggish sedimentation rates, thin sedimentary layers, and notable homogeneity, hinder a comprehensive grasp of the organic matter enrichment (OME) mechanism within these shales. These challenges impede the exploration of unconventional oil and gas resources. This study aims to identify the O3w-S1l1 black shales in the Weiyuan area through a combined approach of organic and inorganic geochemical analyses. By doing so, it delves into the controlling mechanism behind OME in the black shales of the Yangtze foreland basin. The findings of this research reveal that the O3w-S1l1 black shales primarily consist of sapropelic kerogen and exhibit signs of over-maturation, with TOC content ranging from 0.43% to 8.21%. These shales are classified as organic-rich, mainly composed mixed and siliceous lithofacies. The presence of silica in the shales originates mainly from biogenic sources, and the highest TOC content coincides with a Sixs contribution of around 30% to the total silica content. During the late Katian, a global sea level drop led to an oxic paleoenvironment, transitioning into a euxinic paleoenvironment as sea levels rose in the early Rhuddanian. Notably, TOC content exhibited a significant correlation with paleoceanographic conditions (e.g., V/Cr, Ni/Co) and paleoproductivity levels (e.g., P/Al, Babio), while displaying a negative correlation with paleoclimate conditions (e.g., CIA, C-value), terrigenous detrital input intensity (e.g., Sixs, Ti/Al), and sedimentation rate ((La/Yb)N). Specifically, favourable conditions for OME encompass robust reducing seawater conditions, high paleoproductivity, a humid climate, reduced influx of terrigenous debris, and relatively elevated sedimentation rates. Regional tectonic movements (Guangxi movement) and fluctuations in relative sea levels exert influence over the deposition of O3w-S1l1 black shales. This study provides a valuable case study for exploring and developing shale gas resources within the Yangtze foreland basin.